ANALISIS DAN IMPLEMENTASI METODE RAD PADA SISTEM SURAT MASUK DAN SURAT KELUAR BERBASIS WEBSITE STUDI KASUS: INSTITUT SHANTI BHUANA - Firgia, Listra; Nurcahyo, Azriel Christian (Informasi Interaktif, 2021)
Â The number of incoming and outgoing letters that have been received and made in the PROA section of Shanti Bhuana Institute, so that the search for data becomes inaccurate in terms of time and energy with manual systems. This research was conducted with the aim of assisting shanti bhuana institute employees in managing incoming and outgoing letters effectively. This entry and outgoing mail system has the ability to run on computers and mobile phones so that shanti bhuana institute employees can use this system wherever they are. Employees can add, edit, cancel, delete and save incoming and outgoing mail and can print report results based on incoming and outgoing mail. The method used in this study is Rapid Application Development (RAD) whereas for the creation of incoming and outgoing mail systems using php, html and css programming languages. App testing using blackbox testing with results that match expectations from users and researchers.Keywords: incoming mail, outgoing mail, Rapid Application Development.